2006
DOI: 10.1074/jbc.m511918200
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Peptide-mediated Erythromycin Resistance

Abstract: The macrolide antibiotic erythromycin binds at the entrance of the nascent peptide exit tunnel of the large ribosomal subunit and blocks synthesis of peptides longer than between six and eight amino acids. Expression of a short open reading frame in 23 S rRNA encoding five amino acids confers resistance to erythromycin by a mechanism that depends strongly on both the sequence and the length of the peptide. In this work we have used a cell-free system for protein synthesis with components of high purity to clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 24 publications
3
39
0
1
Order By: Relevance
“…A translation of 4-6 amino acids can avoid the possibility of macrolides interacting with the ribosome, and the protein can successfully be translated (Tenson & Mankin, 2001;Tripathi et al, 1998). Lovmar et al (2006) reinforced this model by analyzing the erythromycin dissociation rates with the use of the E-peptide MRLFV. Moreover, the same study showed that alterations in the size of the peptide possess a strong effect on the resistance levels conferred, suggesting that the Leu residue plays a key role in the dissociation of erythromycin.…”
Section: Resistance Mediated By Short Peptidesmentioning
confidence: 99%
“…A translation of 4-6 amino acids can avoid the possibility of macrolides interacting with the ribosome, and the protein can successfully be translated (Tenson & Mankin, 2001;Tripathi et al, 1998). Lovmar et al (2006) reinforced this model by analyzing the erythromycin dissociation rates with the use of the E-peptide MRLFV. Moreover, the same study showed that alterations in the size of the peptide possess a strong effect on the resistance levels conferred, suggesting that the Leu residue plays a key role in the dissociation of erythromycin.…”
Section: Resistance Mediated By Short Peptidesmentioning
confidence: 99%
“…The pentapeptide is removed from the peptidyl-tRNA by a class 1 release factor at the termination step, giving erythromycin ejection from the ribosome at a high probability. Synthesis of the longer heptapeptide with the same five N-terminal amino acids leads neither to ejection of erythromycin nor to drug resistance (14). Our data suggest that even in the absence of termination, an abortive translation event on early UGG or GGG codons can give rise to peptidyl-tRNA where the peptide moiety functions as an E peptide.…”
Section: Vol 189 2007 Abortive Translation and Erythromycin Resistamentioning
confidence: 80%
“…Thus, the Epeptide sequence does not show activity if it is part of a longer protein sequence (14,32,33). It must be in the form of a short peptide since a stop codon or a drop-off-prone NGG codon after this coding sequence is required to promote growth in the presence of erythromycin (Table 1) (14,32). The strains carrying constructs with UGG or GGG at ϩ5 gave a similar relative growth value in the presence of erythromycin, also suggesting E-peptide activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations